2020
DOI: 10.3390/biom10040501
|View full text |Cite
|
Sign up to set email alerts
|

BET Inhibitors Synergize with Carfilzomib to Induce Cell Death in Cancer Cells via Impairing Nrf1 Transcriptional Activity and Exacerbating the Unfolded Protein Response

Abstract: Currently, proteasome inhibitors bortezomib, carfilzomib, and ixazomib are successfully used in clinics to treat multiple myeloma. However, these agents show limited efficacy against solid tumors. Identification of drugs that can potentiate the action of proteasome inhibitors could help expand the use of this therapeutic modality to solid tumors. Here, we found that bromodomain extra-terminal (BET) family protein inhibitors such as JQ1, I-BET762, and I-BET151 synergize with carfilzomib in multiple solid tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Using high-throughput combination screens, we identified several classes of drugs synergizing with BETi in an unbiased manner. Some of these candidates, such as BCL2 inhibitors and HDAC inhibitors, have been shown previously to potentiate the antitumor effects of BETi in SCLC (7,10), while several others, such as inhibitors of cyclin-dependent kinases and carfilzomib, were reported to synergize with BETi in other tumor types (40,41). These earlier studies indirectly validate our results, suggesting shared vulnerabilities between various tumor types.…”
Section: Discussionsupporting
confidence: 89%
“…Using high-throughput combination screens, we identified several classes of drugs synergizing with BETi in an unbiased manner. Some of these candidates, such as BCL2 inhibitors and HDAC inhibitors, have been shown previously to potentiate the antitumor effects of BETi in SCLC (7,10), while several others, such as inhibitors of cyclin-dependent kinases and carfilzomib, were reported to synergize with BETi in other tumor types (40,41). These earlier studies indirectly validate our results, suggesting shared vulnerabilities between various tumor types.…”
Section: Discussionsupporting
confidence: 89%
“…The authors speculated that the JQ1/carfilzomib combination enhances ER stress leading to the activation of CHOP/EBPα, increased BIM transcription, and consequent apoptosis [ 124 ] ( Figure 5 ). Accordingly, a recent study showed that BET inhibitors synergize with carfilzomib in multiple solid tumor cell lines [ 24 ]. In addition, Siegel et al described that the selective BRD4 inhibitor CPI203 showed synergy with bortezomib in resistant cell lines as well as in a primary sample from RRMM patient.…”
Section: Emerging Proteasome Inhibitors Drug Combinations Targetinmentioning
confidence: 99%
“…To this end, the use of combinatorial treatments might allow lowering the dose of inhibitors and therefore, minimize their side-effects. In addition, although PIs failed as single agents for the treatment of solid tumors in clinics [ 16 ], there are accumulating pieces of evidence that the combination of proteasomal inhibition with various drugs could improve the outcome of a wide range of malignant diseases [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond that, in virtue of BET inhibitors, the ability of transcription factor Nrf1 to induce proteasal genes to proteasal inhibition is weakened, hindering the rebound reaction of proteasal activity, which is the key pathway for cells to address protein toxic stress. BET inhibitors have the potential to combine with carfilzomib to treat solid tumors (29).…”
Section: New Mechanismsmentioning
confidence: 99%